Financial Empowerment Through Mindful Spending Program Among Indonesians in Japan - Dhany Efita Sari; Isnaya Arina Hidayati; Suranto; Sri Sumaryati; Septian Enggar Sukmana; Nur Aeni Sa’adah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance financial confidence and mental resilience among Indonesians in Japan through a mindful spending intervention that integrates financial literacy with emotional awareness. Mindful spending emphasizes conscious financial decision-making by aligning spending behavior with personal priorities and psychological well-being. The program was implemented through two online educational sessions and one face-to-face (F2F) workshop using a Brief Intervention Training approach. A total of 29 participants attended the online sessions, which covered the theoretical foundations of mindful spending, financial mental health, and contextual financial practices in Japan. Furthermore, 15 participants participated in the F2F workshop held at the Indonesian Mosque in Tokyo, where they engaged in scenario-based exercises involving promotional discounts, lifestyle spending, and competing financial priorities. Participants documented their responses and reflected on their decision-making processes during group discussions. Data were collected through post-program questionnaires and analyzed using descriptive statistics and correlation analysis. The findings revealed high levels of mindful spending (M = 4.08), mental resilience (M = 4.06), and financial confidence (M = 4.04). Strong positive correlations were identified between mental resilience and financial confidence (r = .80), as well as between financial responsibility and financial confidence (r = .77). Overall, participants reported improved financial awareness and emotional regulation after the program. These results indicate that integrating financial literacy with psychological resilience through mindful spending is an effective approach to empowering the Indonesian diaspora in managing financial challenges abroad.